Nitrogen fertilization directly affects soil bacterial diversity and indirectly affects bacterial community composition. (January 2016) - Zeng, Jun; Liu, Xuejun; Song, Ling; Lin, Xiangui; Zhang, Huayong; Shen, Congcong; Chu, Haiyan
Abstract: Nitrogen (N) deposition influences both above- and below-ground communities and influences ecosystem functioning. However it is not clear about direct or indirect interactions among plants, soils and microbes in response to nitrogen deposition. In this study, the responses of soil bacterial diversity to N enrichment were investigated at surface (0–10 cm) and sub-surface (10–20 cm) soils in a temperate steppe ecosystem. N addition (>120 kg N ha −1  yr −1 ) resulted in a significant shift in bacterial community composition and a decrease in bacterial OTU richness in surface soil, but the effect on the sub-surface layer was far less pronounced, even at the highest addition rate (240 kg N ha −1  yr −1 ). Bacterial OTU richness was significantly correlated with soil and plant characteristics. Hierarchical structural equation modeling showed that soil ammonium availability was responsible for the shift in bacterial richness, whereas the change in bacterial community composition was due to alterations in soil pH and plant composition. These results indicated that N fertilization directly affected soil bacterial richness but indirectly affected bacterial communities through soil acidification and plant community change, indicating distinct controls on soil bacterial diversity and community composition. Our results also suggest that N availability could be a good predictor for the loss of soil bacterial diversity under atmospheric nitrogen deposition. Highlights: N deposition impacts soil bacterial community in grassland. Different controls on soil bacterial diversity and community composition. An integrated mechanism of plant–soil–microbe interactions.